Germinação e desenvolvimento inicial de soja, feijão e nabiça cultivados sob palhada de Digitaria horizontalis - Teixeira, Renake Nogueira [UNESP]; Pereira, Maria Renata Rocha; de Campos, Caio Ferraz [UNESP]; Martins, Dagoberto [UNESP] (My University, 2011)
The study aimed to evaluate the possible inhibitory effects of different concentrations of crabgrass (Digitaria horizontalis Willd.) dry mass incorporated to the soil over the germination and early growth of soybean (Glycine max (L.) Merril.), dry bean (Phaseolus vulgaris L.), and turnip (Raphanus raphanistrum L.). The experimental design adopted was completely random, with four replications where, each one was consisted of a 2.5 L capacity pot. Dry mass of crabgrass at equivalent amounts of 0, 2.5, 5.0 and 10 tha -1 were incorporated into the soil. Crops seedling emergence was checked daily, and germination, speed germination index, mean germination time, relative frequency and synchronization index of germination were computed at the final of 10 days.The height and dry mass of plants were evaluated at 35 days after sowing. The incorporation to the soil of D. horizontalis dry mass caused significant reduction of the height and dry weight of soybean, dry bean and turnip, but were not observed consistent influence over the germination of these species.
Germination and early growth of soybean, dry bean and turnip grown under Digitaria horizontalis straw
Keywords: Crabgrass; Glycine max (L., Merril.); Inhibitory effects; Phaseolus vulgaris L.; Raphanus raphanistrum; Weed